Corrosion behavior of silica-alumina refractories for scrap brass smelter linings. (10th October 2022) - Liu, Wei; Ma, Baozhong; Wang, Ling; Zhao, Qinqing; Zuo, Yi'an; Chen, Yongqiang; Wang, Chengyan
Abstract: Silica-alumina refractories are extensively served as smelter linings for scrap brass due to their good thermal insulation and cost advantage, yet the sudden failure of refractory caused great disturbance to industrial production, such as furnace stoppage. Thus, the corrosion behavior of the silica-alumina refractory exposed to scrap brass slag was researched. Based on the element occurrence states of slag and refractory, the possible reactions between them were first determined to analyze the thermodynamic feasibility. Then, the effects of temperature and time on corrosion behavior were investigated by static laboratory tests. At the slag-refractory interface, the products of continuous reaction were presented. Three parts of the corrosion process were ascertained: (1) The solid oxides (ZnO, CuO, Cu2 O, PbO, etc.) reacted with the compounds of the refractory; (2) The injected liquid composition (NaF, Cu, Pb, Zn, etc.) further reacted with the refractory; (3) The gas phase (fluorine vapor and zinc vapor) invaded and reacted with the interior refractory. Furthermore, it is concluded from the static laboratory tests that the consumption rate of refractory increased by 8.5412 * 10 −4  g/day per 100 °C rise, and an intact brick was entirely corroded in 41.40 days. In the industrial process, continuous chemical corrosion and discontinuous physical damage led to the refractory failure. Lastly, the suggestions for prolonging the service life of refractory were proposed. This study will provide guidance for industrial application of silica-alumina refractory in scrap brass production, which has important implications for the green recycling of scrap brass. Graphical abstract: Image 1 Highlights: The state of elemental occurrence in slag and refractory was investigated. Thermodynamic analysis was used for explaining the test corrosion phenomenon. The effects of temperature and time on corrosion behavior were carried out. The suggestions for prolonging the service life of refractory were put forward.